Phytochemicals screening and phytotoxicity of Strobilanthes crispa Blume (Acanthaceae) leaf extracts - Chen, Chee-Shien; Loke, Chui-Fong; Poh, Theng Loo; Fong, Ee-Lynn; Lai, Oi-Ming; Tan, Siow-Ping (Malaysian Institute of Chemistry, 2024)
Strobilanthes crispa (L.) Blume (S. crispa) is a well-known folklore medicinal plant traditionally used in Malaysia and Indonesia for its diverse range of traditional applications and medicinal properties. While previous studies have established its effectiveness as an anticancer agent against various cancer types, its impact on skin cancer cells remains largely unexplored. In this study, ethanol, hexane, and ethyl acetate leaf extracts of S. crispa were screened for phytochemicals and analyzed for their photocytotoxicity against the A431 human skin squamous carcinoma cell line by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenultetrazolium bromide (MTT) assay. In general, the qualitative analysis indicated the presence of terpenes, alkaloids, phenols, quinones, and chlorophylls in all three crude extracts, while steroids, flavonoids, and anthraquinones were not detected. Upon activation with photodynamic therapy (PDT) treatment, the cell viability decreased. Among the extracts, the hexane crude extract exhibited the highest photocytotoxic activity against the A431 cell line, with an IC50 value of 6.06 ± 0.21 μg/mL, followed by the ethanolic crude extract (IC50 = 8.83 ± 0.55 μg/mL) and the ethyl acetate crude extract (IC50 = 9.37 ± 0.71 μg/mL). However, when tested without PDT treatment, none of the three crude extracts exhibited significant activity against the A431 cell line, even at concentrations as high as 200 μg/mL after 24 hours of incubation in the dark. The results of the present study suggest that S. crispa could serve as a valuable source of photosensitizing agents for photodynamic therapy in cancer treatment.